ELASTISITAS SUBSTITUSI ANTAR FAKTOR PRODUKSI PADA INDUSTRI PENGGERGAJIA KAYU TROPIS (Elasticity of substitution between production factors on tropical sawn timber industry) - Setiasih Irawanti (Jurnal Penelitian Hasil Hutan, 1993)
The objective of this study is to estimate elasticity of substitution, coefficient, and technological parameter on sawn timber industry analyzed is limited to the sawmill belongs to the forest concession.This study used primary data. Analysis of data is conducted using CES production function data analyzed are cross-section primary data on wage, capital value, and production value, collected from 13 forest concession sawmills.The result of CBS production function shows that the elasticity of substitution 0 = 0,5247, it means that power of substitution between capital and labor in sawn timber industry is low. Technological coefficient A = 4.9654 shows that the increase of sawn timber production level is about 5 times of the increasing capital and labor inputs. Distribution parameter β = 0,7114 shows that relative contribution of capital input is about 71 % and labor input is about 29% on sawn timber production. Sawn timber industry is a capital intensive, which means that the increase of production is more effective through the increasing of capital input. The revenue of sawn timber industry is distributed more to the owner of capital than to labor.